Isu Kesehatan Mental dan Persepsi Followers Pada akun Instagram @Ibunda.id - Leksono, Levana Fransin Aulia; Febrianita, Roziana (Jurnal Ilmiah Wahana Pendidikan, 2024)
Mental health is a supporting factor in a person's survival so that they can continue to think rationally and advanced, which has the essence of being a supporting factor for social activities such as communication and interaction. Social media is here to help take preventive measures for people experiencing mental health by providing information and education about the symptoms of mental health disorders. One of the social media that disseminates information and education on mental health issues is the Instagram account @ibunda.id. The aim of this research is to look at followers' perceptions of mental health issues on the Instagram account @ibunda.id. This research uses a qualitative method with a case study approach. The data collection technique was carried out using interview techniques which were analyzed using the Miles and Huberman interactive model. The research results show that perception is formed through the processes of sensation, attention and interpretation. Instagram followers @ibunda.id received the message content of the post well. Each informant has an interest in certain mental health issues based on their personal experiences and feelings. This has received positive action in changing their mental and mental state for the better thanks to insights from Instagram posts @ibunda.id.